Peru: The Strength of its History - Amayo Zevallos, Enrique (2006)
Each and every one of the South American societies have peculiarities and specificities. In the Peruvian case, its peculiarity is the weight of its history. Its specificity: that it is impossible to explain much of the affairs of its present without considering its remote antiquity. In other words, the destruction of its Indigenous Civilization, made by the Spanish (Indigenous America as a whole, since the end of the 15th century, was destroyed by the Europeans as part of the expansion and domination of the West over the World) and known as Conquest, it is just a different and new stage in a millennial historical-social construction process. This context is important to understand Peruvian society and culture in the last half century.